2018
DOI: 10.1186/s40816-018-0075-x
|View full text |Cite|
|
Sign up to set email alerts
|

Phytochemical studies, antiangiogenic, anti-inflammatory and antioxidant activities of Scyphocephalium ochocoa Warb. (Myristicaceae), medicinal plant from Gabon

Abstract: Background: The search for new anti-cancer molecules is one of the main concerns of oncology researchers. Scyphocephalium ochocoa is a plant of Myristicaceae family, used in traditional medicine against inflammatory diseases and several types of cancer. It is well established that free radicals, chronic inflammation and angiogenesis play an important role in initiation, tumor progression and metastasis formation. The aim of this study was to carry out a phytochemical screening, to determine the phenolic compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…These data indicate that MEJSL could contain an anti-inflammatory property. Previous studies have demonstrated that plant extracts with antiinflammatory property possess the capacity to inhibit protein denaturation and stabilize cell membrane against lysis [27,28]. Protein denaturation is a biochemical reaction that occurs during chronic inflammatory response which could result into loss of tissue function [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that MEJSL could contain an anti-inflammatory property. Previous studies have demonstrated that plant extracts with antiinflammatory property possess the capacity to inhibit protein denaturation and stabilize cell membrane against lysis [27,28]. Protein denaturation is a biochemical reaction that occurs during chronic inflammatory response which could result into loss of tissue function [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Out of three in vivo studies, one used chloroform extract (Olajide et al, 1999), one exhibited gastric mucosal ulceration with seed oil and indomethacin (Olajide et al, 2000) while the other was conducted only on male mice (Carvalho et al, 1999). In vitro assay of antiinflammatory activity was carried out with only extracts (Ngoua‐Meye‐Misso et al, 2018), whereas reviewed references lacked effective concentration of Kombo butter of Pycnanthus angolensis (Gustafson et al, 2013) and biomarkers of Knema glauca (Rangkaew et al, 2009).…”
Section: Pharmacologymentioning
confidence: 99%
“…The total phenol content of the crude extracts or fractions was determined by the method of Folin-Ciocalteu [18]. The absorption is read spectrophotometer at the wavelength of 735 nm.…”
Section: Determination Of Total Phenolsmentioning
confidence: 99%